Танцы марионеток - Михалкова Елена Ивановна (Настоящий детектив Елены Михалковой, 2015)
Экземпляры: ф.7 (20160929) / Инвентарный номер: 41663 / Цена: / Авт.знак: М 69 / ГРНТИ: 17.82 / ББК: 84(2Рос-Рус)6-44